Revitalisasi Ekonomi Islam: Mengembangkan Model Ekonomi Hijau Berbasis Keadilan dan Etika Islam - Dewi, Arlinta Prasetian; Ulin Nuhaa, Muhammad Afif (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2025)
Green economy, which emphasizes sustainability and efficient management of natural resources, is now a major concern amidst the global environmental crisis. This concept is in line with the principles of Islamic economics, which emphasize social justice, fair distribution, and wise management of natural resources. This article aims to explore the potential of Islamic economics in developing a green economic model based on Islamic justice and ethics. Through a literature review and in-depth analysis, this study identifies how Islamic economic principles can be integrated into green economic development. The results show that the Islamic economic approach can support the implementation of a green economy by emphasizing the balance between economic interests and environmental sustainability. This article also provides policy recommendations that can be implemented to advance a green economy within the framework of Islamic economics.